Nasionalisme, Demokratisasi, dan Sentimen Primordialisme di Indonesia: Problematika Identitas Keetnisan Versus Keindonesiaan (Studi Kasus Aceh, Papua, Bali, dan Riau) - Noor, Firman (Pusat Penelitian Politik, 2008)
This research explores theoretically the reasons behind the emergence ofprimordial sentiment in Indonesia in the era of democratization The research indicates six factors that determine this phenomenon namely the continuation of incorrect interpretation about the true meaning of Indonesia the existence offormalistic understanding on the role ofreligion in the state economical disparity political injustice and state domination in interpreting national symbols In this regards the research finds that mismanage in governing people and the repressive tendency ofprevious government as the trigger of the emergence ofprimordial sentiment in reformasi era.